Influence of hurdling clearance on sprint mechanical properties in high-level athletes - Jiménez-Reyes, P.; Casado, A.; González, J. E.; Rodríguez-Fernández, C. (The Journal of Strength and Conditioning Research, 2022)
Short hurdling races are sprint races in which athletes must also clear 10 hurdles. Assessing the force-velocity (F-V) profile in sprinting has been found useful for implementing individualized training programs and determining the mechanical effectiveness in force application. This study therefore compared the sprint mechanical F-V profile between flat and hurdle conditions to distinguish which mechanical capacity (i.e., maximum force [F0], maximum velocity [V0], or maximum power [Pmax]) is required to optimize performance in hurdling races. Twenty-two athletes (10 men and 12 women, aged: 22.4 ± 3.6 years old) competing at the national and elite performance levels conducted 2 maximal sprints of 40 m in both flat and hurdle conditions. F0, V0, FVslope, Pmax, and decrease and maximal ratio of horizontal force (DRF and RFpeak, respectively) were assessed for each condition. A higher F0 (effect size [ES] = 1.69) and a lower V0 (ES = 2.08), DRF (ES = 3.15) and RFpeak (ES = 1.31) were found in the hurdle condition than in the flat condition. No significant differences were observed between conditions for Pmax (ES = 0.01). These results support the potential of using the F-V profile to monitor sprint mechanics to optimize specific and individualized sprint training programs for hurdlers and sprinters. Coaches of hurdlers should thus consider implementing in their training routines exercises that were found to be effective on the development of F0, such as heavy load resisted sprints.